1982
DOI: 10.1128/aac.22.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of amoxicillin and clavulanic acid administered alone and in combination

Abstract: The pharmacokinetics of amoxicillin and clavulanic acid, administered alone and in combination, were studied in six male and six female normal human volunteers. Each ingested 500 mg of amoxicillin or 125 mg of clavulanic acid or the above agents in combination in randomized sequences. The results indicate that most of the parameters tested for either substance are essentially independent of the presence of the other one.Microorganisms which are resistant to certain antibiotics are increasingly posing problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 12 publications
6
39
1
1
Order By: Relevance
“…Confirming results previously reported by Zhang et al (36) for strain H37Rv, we demonstrated that the ␤-lactamase activity of its avirulent counterpart, strain H37Ra, was inhibited by clavulanic acid and sulbactam, with IC 50 s for hydrolysis of nitrocephin of 0.2 and 1.3 g/ml, respectively. These concentrations are well within the therapeutic ranges of these inhibitors (1,11).…”
Section: Resultsmentioning
confidence: 55%
“…Confirming results previously reported by Zhang et al (36) for strain H37Rv, we demonstrated that the ␤-lactamase activity of its avirulent counterpart, strain H37Ra, was inhibited by clavulanic acid and sulbactam, with IC 50 s for hydrolysis of nitrocephin of 0.2 and 1.3 g/ml, respectively. These concentrations are well within the therapeutic ranges of these inhibitors (1,11).…”
Section: Resultsmentioning
confidence: 55%
“…The dose levels of amoxicillin and clavulanic acid used were chosen because in the mouse they produced concentrations in blood and tissue which were similar to those obtainable in humans (1,26). At 4 h after infection, the peak blood level of amoxicillin given alone was 13.7 ± 2.8 l.g/ml at 30 min and of clavulanic acid alone was 12.8 ± 1.7 ,.g/ml, falling to 1.25 + 0.97 and 1.37 + 0.80 ,ug/ml, respectively, by 120 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of plasma samples (n ϭ 1,152) collected from 48 closely monitored, healthy volunteers in two bioequivalence studies allowed the development and subsequent validation of LSS models by using several different procedures. The results show that the AUC 0-ϱ of amoxicillin, following administration of single oral doses (500 ) for amoxicillin in 11 previously published studies (1,3,7,10,13,14,(17)(18)(19)(20)26), and the corresponding AUC 0-ϱ derived from the three-point LSS model developed for the reference capsule formulation in the present study (Table 3, (Table 2). The statistical principle of parsimony advises in favor of models with fewer parameters; thus, we settled for three-sample regressions for independent estimation of amoxicillin's AUC 0-ϱ .…”
Section: Discussionmentioning
confidence: 54%
“…The robustness of the three-point LSS regression equation derived from the capsule formulation data set as a predictor of the plasma amoxicillin AUC 0-ϱ was confirmed when tested on data from 11 published studies (1,3,7,10,13,14,(17)(18)(19)(20)26), encompassing a large range of amoxicillin single doses (250 to 1,000 mg) and AUC 0-ϱ 's (9 to 55 g ⅐ h ⅐ ml Ϫ1 ). This result not only validates our proposed three-point LSS model but also extends its applicability to a variety of experimental conditions, both clinical and analytical, which prevailed in the 11 studies examined.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation